A lack of sexual autonomy is associated with increased loneliness in young mothers - Chelsea Bunke; Tara Keck (BMC Women's Health)
Abstract Background Loneliness is a significant risk factor for both mental and physical health issues, including depression and increased mortality. Loneliness is reported at higher levels during life transitions, such as the transition to motherhood. Loneliness in mothers has far-reaching detrimental impacts on both mother and child, such as an increased risk of maternal depression and child abuse. Understanding the impact of different risk factors for loneliness, specifically in young mothers, may inform potential interventions for this at-risk group. The aim of this study was to determine whether mothers were lonelier than childfree women, and whether there are different risk factors for loneliness in mothers relative to childfree women, both for gender-associated and established risk factors for loneliness. Methods This cross-sectional study included partnered mothers and partnered childfree women between the ages of 20 and 29 from the 2020 Generations and Gender Survey (GGS) in the Republic of Moldova. The De Jong Gierveld Loneliness Scale was used to assess overall, emotional, and social loneliness. A total of 11 potential risk factors were considered, across gender, well-being, relationships, and household status. Depending on the nature of the variables and their distributions, Wilcoxon rank-sum tests or Spearman correlation coefficients were used to assess loneliness risk factors for partnered mothers and childfree women. Results Data from 396 mothers and 113 childfree women in the Republic of Moldova were analysed in this study. There was no significant difference between the mean overall, emotional, or social loneliness scores in partnered mothers and childfree women. A lack of sexual autonomy was a risk factor associated with social loneliness in young mothers, but not in childfree women. This was the only gendered risk factor that differed between populations. Other gendered risk factors were not significant for any types of loneliness in either population. There were differences between mothers and childfree women in several established risk factors for loneliness. Conclusion Mothers were not lonelier than childfree women in this study, but a lack of sexual autonomy was a risk factor associated with loneliness only in mothers.